Modified ternary material as well as preparation method and application thereof
By forming shallow doped regions of non-cobalt metal and cobalt gradient doped regions in ternary materials and forming a cladding layer on the surface, the problems of poor rate performance and fast growth of cyclic DCR of low-cobalt ternary cathode materials are solved, and the energy density and cyclic performance of the material are improved.
Patent Information
- Application Number
- CN202510142802.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-10
AI Technical Summary
Low-cobalt single-crystal ternary cathode materials have problems such as poor rate performance and fast growth of cyclic DCR, which cannot meet the demand for lithium-ion batteries of electric vehicles.
By mixing the ternary material matrix with a non-cobalt metal source to form a shallow doped region of non-cobalt metal, the doping depth of cobalt elements is reduced, and a cobalt gradient doped region with decreased cobalt element concentration is formed through subsequent sintering, and finally a cladding layer is formed on the surface to prepare a modified ternary material.
The significance of the cobalt concentration gradient structure is achieved, the energy density and cyclic performance of the material are improved, and the ion transfer rate is improved and side reactions are prevented through the cladding layer is ensured, ensuring the effective performance of cobalt elements.
Smart Images

Figure CN119601646A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials and relates to a modified ternary material and a preparation method and application thereof. Background Art
[0002] Lithium nickel cobalt manganese oxide positive electrode material, also known as ternary material, has the advantages of high energy density and good cycle performance. It is one of the most promising positive electrode materials for lithium-ion batteries.
[0003] As the global electric vehicle market continues to heat up in recent years, the demand for ternary lithium-ion batteries has increased significantly. However, as the global competition for cobalt resources becomes increasingly fierce and the price of cobalt raw materials continues to rise, the trend of low-cobalt ternary materials is becoming more and more obvious. Although reducing the content of cobalt can effectively control costs, cobalt plays an important role in stabilizing the layered structure of materials, inhibiting lithium-nickel mixing, and enhancing the ionic conductivity of positive electrode materials. As a result, low-cobalt single-crystal ternary positive electrode materials have poor rate performance and fast cycle DCR growth, which cannot meet the current demand for lithium-ion batteries in electric vehicles.
[0004] At present, the low-cobalt route is mostly to reduce the cobalt content at the precursor (such as cobalt manganese hydroxide) end, and then make up for the poor battery cycle performance and high internal resistance caused by low-cobalt materials through bulk doping (such as Zr doping) and surface modification (such as Al coating) of other elements. There is also a strategy of late cobalt supplementation at the positive end. For example, CN112750999A discloses a cobalt-coated ternary positive electrode material and a preparation method thereof, which is obtained by mixing a high-nickel cobalt-free positive electrode material intermediate with a nano-cobalt-containing compound and then calcining it, and coating the outer surface of the high-nickel cobalt-free multi-element positive electrode material intermediate to form a cobalt-containing compound. By coating the surface with cobalt elements, the material structure can be stabilized.
[0005] In fact, the effect of cobalt coating on improving material performance is closely related to the gradient structure formed by the cobalt element inside the particle phase. For example, the conventional fire coating used in CN112750999A cannot accurately control the Co coating gradient structure. When the temperature is too high, Co tends to be incorporated into the bulk phase, which can neither reduce the overall content of Co nor form an obvious gradient distribution effect. When the coating temperature is too low, the cobalt element tends to stagnate on the surface of the material, which is equivalent to forming a coating layer, and the improvement of material performance itself is relatively limited.
[0006] Therefore, it is still necessary to develop and research solutions for low-cobalt ternary materials in order to accurately control and optimize the gradient distribution of the cobalt element, thereby effectively improving the energy density and cycle performance of the modified ternary materials. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a modified ternary material and its preparation method and use, the preparation method comprising mixing a ternary material matrix with a non-cobalt metal source to form a non-cobalt metal shallow doping region to obtain a first modified material; then mixing with a cobalt source and performing a second sintering to form a cobalt gradient doping region with a decreasing cobalt element concentration to obtain a second modified material; finally mixing with a coating agent and performing a third sintering to form a coating layer on the surface of the second modified material to obtain the modified ternary material. The present invention first prepares a non-cobalt metal shallow doping region, and uses the non-cobalt metal element with a larger ion radius enriched in the shallow surface position of the ternary material matrix as a barrier to the subsequent cobalt element doping, effectively reducing the doping depth of the cobalt element, and then constructing a bulk doping structure with a more significant cobalt concentration gradient, which is conducive to further improving the power performance and thermal stability of the ternary material.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a modified ternary material, comprising the following steps:
[0010] (1) mixing a ternary material matrix with a non-cobalt metal source, and performing a first sintering to form a non-cobalt metal shallow doping region from the surface of the ternary material matrix to the inside, thereby obtaining a first modified material; wherein the ion radius of the non-cobalt metal element is greater than the ion radius of the cobalt element;
[0011] (2) mixing the first modified material with a cobalt source and performing a second sintering to form a cobalt gradient doping region with a decreasing cobalt element concentration from the surface to the inside of the first modified material, thereby obtaining a second modified material;
[0012] (3) The second modified material is mixed with a coating agent, and subjected to a third sintering to form a coating layer on the surface of the second modified material, thereby obtaining the modified ternary material.
[0013] In the preparation method of the present invention, the non-cobalt metal source with a larger metal ion radius is first sintered with the ternary material matrix in order to pre-directionally incorporate the corresponding non-cobalt metal element with a larger ion radius into the lattice of the ternary material matrix, and the doping depth is located in the shallow surface layer to form a barrier to block the subsequent cobalt doping. Based on this, the doping depth of the cobalt element can be effectively reduced during the second sintering, thereby limiting more cobalt to the shallow surface layer, so that the cobalt concentration in the shallow layer is high, the cobalt concentration gradient changes rapidly, and the gradient difference is large, that is, the cobalt concentration gradient in the shallow layer is more obvious, and in the non-shallow layer area (i.e., the boundary of the shallow layer to the center of the particle), the cobalt concentration gradient changes slowly and the gradient difference is small. Therefore, from the overall point of view, although cobalt is still bulk doped, the overall cobalt concentration gradient structure (i.e., the cobalt gradient doping area) is also more significant because of the difference in gradient structure in the specific area. It can be seen that this specific cobalt concentration gradient structure is different from the structure of uniformly changing cobalt concentration gradient from the center of the particle to the surface manufactured by the conventional cobalt coating process.
[0014] Based on the specific cobalt concentration gradient structure formed by the present invention, since the concentration of cobalt elements is high in the shallow area, especially on the surface, it can improve the ionic conductivity of the material and thus reduce the material impedance and increase the energy density; at the same time, the cobalt concentration gradient doping structure formed by the particles as a whole is also conducive to improving the cycle performance. On this basis, the present invention can repair the surface of the material through the third sintering coating to obtain a modified ternary material with a complete coating layer, which can not only improve the ion transfer rate, but also reduce the side reactions between the particles and the electrolyte, and prevent the cobalt concentration gradient distribution from being destroyed, thereby ensuring that the gradient-doped cobalt element plays its due role. The preparation method is simple in process, fully compatible with existing production line mass production equipment, and the production process is easy to control, which is suitable for large-scale mass production.
[0015] It should be emphasized that if the shallow surface doping of non-cobalt metal elements is not implemented, and the ternary material matrix is directly doped with cobalt, under the same other process conditions, the doping depth of the cobalt element will be deepened, the overall difference in the cobalt concentration gradient will be reduced, and the improvement of the material energy density and impedance performance will be small; at this time, in order to reduce the doping depth of the cobalt element, the sintering (i.e., the second sintering) temperature is often selected to be reduced, and due to the low temperature, some cobalt elements will stagnate on the surface or surface layer of the material and cannot effectively penetrate into the bulk phase. These cobalt elements are highly active and will cause the high-temperature storage gas production and charge retention performance of the battery cell to deteriorate seriously. In other words, the existing technical methods cannot well balance the contradiction between the excessive depth of cobalt doping and the cobalt staying on the surface or surface layer of the particles. The present invention provides an effective improvement plan for the above-mentioned problem, which can implement better control of the gradient doping of cobalt, thereby further improving the electrochemical performance of the modified ternary material.
[0016] It should also be noted that the doping of non-cobalt metal elements in the shallow layer does not simply attach to the surface of the particles. The amount of non-cobalt metal elements added is small, and the doping depth from the surface is shallow, and there is no need to limit the non-cobalt metal elements to form a concentration gradient structure. The ion radius of the non-cobalt metal element must be larger than the ion radius of the cobalt element, otherwise the incorporation of the cobalt element cannot be effectively suppressed.
[0017] It should also be noted that the formation of the coating layer in step (3) of the preparation method of the present invention has no effect on the already formed cobalt concentration gradient distribution. If only steps (1) and (2) are performed, the obtained second modified material is also advantageous over the ternary material matrix uniformly doped with cobalt in the prior art, especially in terms of cycle and storage performance. Considering the overall performance of the obtained modified ternary material, especially the optimization of capacity performance, it is more important to perform step (3) to form the coating layer.
[0018] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0019] As a preferred technical solution of the present invention, in step (1), the non-cobalt metal element in the non-cobalt metal source includes at least one of W, Mo or Nb.
[0020] Preferably, the non-cobalt metal source comprises an oxide.
[0021] Preferably, the particle size D of the non-cobalt metal source is 50 It is 0.02~1μm, for example, 0.02μm, 0.05μm, 0.08μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0022] In the present invention, the particle size D of the material 50 It can be measured by Malvern laser particle size analyzer.
[0023] Preferably, the mass ratio of the non-cobalt metal element in the non-cobalt metal source to the ternary material matrix is (0.0005~0.005):1, for example, 0.0005:1, 0.0008:1, 0.001:1, 0.0013:1, 0.0015:1, 0.0018:1, 0.002:1, 0.0023:1, 0.0025:1, 0.0028:1, 0.003:1, 0.0033:1, 0.0035:1, 0.0038:1, 0.004:1, 0.0043:1, 0.0045:1, 0.0048:1 or 0.005:1, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0024] In the present invention, when the amount of non-cobalt metal elements added is too small, the incorporation of cobalt elements cannot be effectively prevented, and an ideal cobalt concentration gradient structure cannot be obtained; and when the amount of non-cobalt metal elements added is too large, the kinetic properties of the material will be affected, and the energy density and initial DCR will deteriorate to a certain extent.
[0025] Preferably, the ternary material matrix comprises a nickel-cobalt-manganese ternary material, the chemical formula of which is Li(Ni x Co y Mn z )O2, 1>x≥0.6, for example, x can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or 0.95, etc.; 0.2≥y>0, for example, y can be 0.2, 0.18, 0.15, 0.13, 0.1, 0.08, 0.06, 0.04, 0.02 or 0.01, etc.; 0.4≥z>0, for example, z can be 0.4, 0.35, 0.3, 0.25, 0.2, 0.15, 0.1, 0.05, 0.03 or 0.01, etc., and x+y+z=1, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0026] It should be noted that the preparation method of the present invention is mainly aimed at nickel-cobalt-manganese ternary materials with low cobalt (0.2≥y>0), but the purpose of the present invention is to form a concentration gradient distribution of the cobalt element. Therefore, it can also have a certain degree of optimization effect on other types of nickel-cobalt-manganese ternary materials, such as NCM523. With the intention and purpose of the present invention understood, reasonable selection can be made according to actual needs.
[0027] Preferably, the method for preparing the ternary material matrix comprises mixing a lithium source with a nickel-cobalt-manganese hydroxide precursor, and calcining the mixture in an oxygen-containing atmosphere to obtain the ternary material matrix.
[0028] The present invention does not specifically limit the specific preparation method of the ternary material matrix, and is preferably a high-temperature solid-phase sintering method commonly used in industrialization. The high-temperature solid-phase sintering method is to mix the ternary material matrix with a non-cobalt metal source for the first sintering to achieve the doping of the non-cobalt metal source in the shallow layer. The non-cobalt metal source and the ternary material matrix precursor (such as nickel cobalt manganese) cannot be mixed and sintered in advance during the synthesis of the ternary material matrix. In this way, due to the high pre-sintering temperature of the synthetic ternary material matrix, the non-cobalt metal element will directly enter the center of the bulk phase, and it is impossible to control it to be distributed only in the shallow layer, and thus it cannot play a blocking role in the subsequent doping of the cobalt element, and the concentration gradient doping effect of the cobalt element cannot be formed.
[0029] Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium nitrate; the nickel cobalt manganese hydroxide precursor includes Ni x Co y Mn z (OH)2, 1>x≥0.6, 0.2≥y>0, 0.4≥z>0, and x+y+z=1, for example, x can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or 0.95, etc.; 0.2≥y>0, for example, y can be 0.2, 0.18, 0.15, 0.13, 0.1, 0.08, 0.06, 0.04, 0.02 or 0.01, etc.; 0.4≥z>0, for example, z can be 0.4, 0.35, 0.3, 0.25, 0.2, 0.15, 0.1, 0.05, 0.03 or 0.01, etc., and x+y+z=1, but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0030] Preferably, the molar ratio of the lithium element in the lithium source to the transition metal element in the nickel-cobalt-manganese oxide is (1.00-1.08):1, for example, 1.00:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1 or 1.08:1, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0031] Preferably, the calcination temperature is T0, T0 = 700-1000°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, etc., the time is 6-15h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, etc., and the oxygen concentration in the oxygen-containing atmosphere is 70%-100%, for example, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0032] As a preferred technical solution of the present invention, in step (1), the temperature of the first sintering is T1, T1=700-900°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C or 900°C, and the time is 4-15h, for example, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0033] If the sintering temperature in step S1 is too high, more metal elements will enter the center of the bulk phase, and thus cannot hinder the further incorporation of cobalt elements in the subsequent step S2, and thus cannot obtain the expected cobalt concentration gradient structure material. If the sintering temperature in S1 is too low, non-cobalt elements tend to stay on the surface of the ternary material matrix in the form of metal oxides, and also cannot effectively hinder the further incorporation of cobalt elements.
[0034] As a preferred technical solution of the present invention, in step (1), the coverage range of the non-cobalt metal superficial doping area starts from the surface of the ternary material matrix to the position of 80% to 99% of the center of the ternary material matrix to the surface, for example, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98% or 99%, etc., that is, this position is the boundary of the non-cobalt metal superficial doping area inside the particle, but is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0035] In the present invention, the non-cobalt metal is doped in the shallow layer, and the thickness of the shallow layer or the depth of the non-cobalt metal element doping is from the surface to 80% to 99% of the position from the center of the material to the surface, and the part between them is doped with the non-cobalt metal element. However, the boundary position cannot be 100%, that is, the non-cobalt metal element cannot only be attached to the surface, but must be doped into the shallow layer.
[0036] As a preferred technical solution of the present invention, in step (2), a flux is used to mix the first modified material and the cobalt source, and then the second sintering is performed.
[0037] Preferably, the flux includes a compound containing at least one of Li, B, P or F.
[0038] Preferably, the flux includes at least one of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), aluminum fluoride (AlF3), lithium fluoride (LiF), boron oxide (B2O3), phosphoric acid (H3PO4) or lithium phosphate (Li3PO4).
[0039] Preferably, the mass ratio of the flux to the cobalt source is (0.01~0.6):1, for example 0.01:1, 0.05:1, 0.08:1, 0.1:1, 0.13:1, 0.15:1, 0.18:1, 0.2:1, 0.23:1, 0.25:1, 0.28:1, 0.3:1, 0.33:1, 0.35:1, 0.38:1, 0.4:1, 0.43:1, 0.45:1, 0.48:1, 0.5:1, 0.53:1, 0.55:1, 0.58:1 or 0.6:1, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0040] Preferably, the cobalt source includes at least one of cobaltous hydroxide (Co(OH)2), cobalt oxyhydroxide (CoOOH) or cobalt trioxide (Co3O4).
[0041] Preferably, the particle size D of the cobalt source is 50 It is 0.05~1.2μm, for example, 0.05μm, 0.06μm, 0.07μm, 0.08μm, 0.09μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm or 1.2μm, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0042] Preferably, the mass ratio of the cobalt element in the cobalt source to the first modifying material is (0.005~0.03):1, for example 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, 0.011:1, 0.012:1, 0.013:1, 0.014:1, 0.015:1, 0.016:1, 0.017:1, 0.018:1, 0.019:1, 0.02:1, 0.022:1, 0.024:1, 0.026:1, 0.028:1 or 0.03:1, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0043] As a preferred technical solution of the present invention, in step (2), the temperature of the second sintering is T2, T2 = 650-850°C, for example, 650°C, 660°C, 680°C, 700°C, 720°C, 740°C, 750°C, 780°C, 800°C, 820°C or 850°C, and the time is 4-15h, for example, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0044] It should be noted that in the present invention, the concentration gradient distribution of the cobalt element is affected by the second sintering temperature in addition to the influence of the non-cobalt metal superficial doping. However, the temperature of the second sintering is related to the specific selection of the ternary material matrix. When the component content of the ternary material matrix changes, the most suitable second sintering temperature will change within 650-850°C, so it should be reasonably adjusted and selected.
[0045] Normally, T1>T2℃, preferably T1-T2>40℃, for example, T1-T2 is 42℃, 45℃, 48℃, 50℃, 52℃, 55℃, 58℃, 60℃, 63℃, 65℃, 68℃, 70℃, 72℃, 75℃, 78℃ or 80℃, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0046] As a preferred technical solution of the present invention, in the second modified material, the concentration of cobalt element on the surface is recorded as a, the concentration of cobalt element at 80% of the position from the center to the surface is recorded as b, and the concentration of cobalt element at 50% of the position from the center to the surface is recorded as c; the concentration of cobalt element in the ternary material matrix is recorded as d; the cobalt element concentration refers to the percentage of the amount of cobalt element in the total amount of nickel, cobalt and manganese elements, then, 10>(ab) / (cd)>3, for example, (ab) / (cd) can be 3.2, 3.5, 3.8, 4, 4.3, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, 6.3, 6.5, 6.8, 7, 7.3, 7.5, 7.8, 8, 8.2, 8.5, 8.8, 9, 9.2, 9.5 or 9.8, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0047] As a preferred technical solution of the present invention, in step (3), the coating agent includes a compound containing at least one of Al, Zr, W, Ti, Mg, Nb, Zn, Fe, La, B, P or F.
[0048] Preferably, the mass ratio of the metal element in the coating agent to the second modifying material is (0.0001~0.003):1, for example 0.0001:1, 0.0003:1, 0.0005:1, 0.0008:1, 0.001:1, 0.0012:1, 0.0014:1, 0.0016:1, 0.0018:1, 0.002:1, 0.0022:1, 0.0024:1, 0.0026:1, 0.0028:1 or 0.003:1, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0049] Preferably, the temperature of the third sintering is T3, T3 = 250~550℃, for example 250℃, 280℃, 300℃, 330℃, 350℃, 380℃, 400℃, 420℃, 450℃, 480℃, 500℃, 520℃ or 550℃, etc., and the time is 6~15h, for example 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, etc., but is not limited to the listed values, other values not listed within the above numerical range are also applicable.
[0050] In a second aspect, the present invention provides a modified ternary material, wherein the modified ternary material is obtained according to the preparation method described in the first aspect.
[0051] In a third aspect, the present invention provides a battery comprising the modified ternary material described in the second aspect.
[0052] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0053] The preparation method of the present invention pre-directionally dopes non-cobalt metal elements with larger ionic radius into the shallow layer of the ternary material matrix to form a barrier to block subsequent cobalt doping, which can effectively reduce the doping depth of cobalt elements and thus limit more cobalt to the shallow surface of the particles, so that the cobalt concentration gradient structure has the characteristics of high cobalt concentration in the shallow layer, fast cobalt concentration gradient change, and large gradient difference, while in the non-shallow layer area, the cobalt concentration gradient changes slowly and the gradient difference is small, which is different from the relatively uniform cobalt concentration change structure manufactured by the conventional cobalt coating process. After the second sintering to dope the cobalt element into the bulk phase and form a concentration gradient structure, the cobalt element has a high proportion on the surface of the material due to the gradient decrease of the cobalt element concentration from the outside to the inside, which can improve the ionic conductivity of the material and thus reduce the material impedance and increase the energy density; at the same time, the cobalt concentration gradient doping structure formed by the particles as a whole is also conducive to improving the cycle performance. Finally, the surface of the material can be repaired by coating through the third sintering to obtain a modified ternary material with a complete coating layer, which can not only improve the ion transmission rate, but also reduce the side reaction between the particles and the electrolyte, prevent the cobalt concentration gradient distribution from being destroyed, thereby ensuring that the gradient doped cobalt element plays its due role. The preparation method is simple in process, fully compatible with existing production line mass production equipment, and the production process is easy to control, which is suitable for large-scale mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a test diagram of the content distribution of cobalt element in the modified ternary materials obtained in Example 1, Example 5, Example 8, Example 10 and Comparative Example 1.
[0055] Figure 2 Schematic diagram of the cross section of the first modified material obtained in step (1) of the preparation method of Example 1.
[0056] Figure 3 It is a schematic diagram of the contour comparison of the cobalt concentration gradient distribution of the modified ternary material obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0058] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0059] Example 1
[0060] This embodiment provides a method for preparing a modified ternary material, the preparation method comprising:
[0061] (1) First prepare the ternary material matrix, lithium hydroxide as the lithium source and nickel cobalt manganese hydroxide precursor Ni 0.75 Co0.05 Mn 0.25 The molar ratio of lithium in the lithium source to the transition metal in the nickel-cobalt-manganese oxide is 1.04:1, and then calcined at 910°C for 12h in an oxygen atmosphere to obtain a single crystal ternary material matrix Li(Ni 0.75 Co 0.05 Mn 0.25 )O2;
[0062] The ternary material matrix and particle size D 50 The non-cobalt metal source niobium pentoxide with a mass ratio of 0.3 μm to the non-cobalt metal element niobium in the non-cobalt metal source and the ternary material matrix is 0.001:1; then, a first sintering is performed at 850° C. for 8 hours in an air atmosphere to form a non-cobalt metal superficial doping region from the surface to the inside of the ternary material matrix, and the agglomerated material is put into a jet mill and crushed until the particle size D 50 =3.9 μm, and the first modified material is obtained;
[0063] (2) The obtained first modified material and particle size D 50 A cobalt source cobalt hydroxide with a diameter of 0.6 μm is mixed with a flux boric acid, wherein the mass ratio of the flux to the cobalt source is 0.02:1, and the mass ratio of the cobalt element in the cobalt source to the first modified material is 0.01:1, and then a second sintering is performed at 800° C. for 8 hours in an oxygen atmosphere to form a cobalt gradient doping region with a decreasing cobalt element concentration from the surface to the inside of the first modified material, thereby obtaining a second modified material;
[0064] (3) The obtained second modified material is mixed with a coating agent of titanium dioxide, wherein the mass ratio of the metal element titanium in the coating agent to the second modified material is 0.0012:1, and a third sintering is performed at 400° C. for 10 hours in an air atmosphere to obtain a modified ternary material.
[0065] Example 2
[0066] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (1), the mass ratio of the non-cobalt metal element niobium in the non-cobalt metal source to the ternary material matrix is adjusted from 0.001:1 to 0.0005:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0067] Example 3
[0068] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (1), the mass ratio of the non-cobalt metal element niobium in the non-cobalt metal source to the ternary material matrix is adjusted from 0.001:1 to 0.002:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0069] Example 4
[0070] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (1), the mass ratio of the non-cobalt metal element niobium in the non-cobalt metal source to the ternary material matrix is adjusted from 0.001:1 to 0.005:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0071] Example 5
[0072] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (1), the non-cobalt metal source is replaced by tungsten trioxide instead of niobium pentoxide. Except for the above, other conditions are exactly the same as those in Example 1.
[0073] Example 6
[0074] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (1), the non-cobalt metal source is replaced by molybdenum trioxide instead of niobium pentoxide. Except for the above, other conditions are exactly the same as those in Example 1.
[0075] Example 7
[0076] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (2), the mass ratio of the cobalt element in the cobalt source to the first modified material is adjusted from 0.01:1 to 0.005:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0077] Example 8
[0078] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (2), the mass ratio of the cobalt element in the cobalt source to the first modified material is adjusted from 0.01:1 to 0.02:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0079] Example 9
[0080] This embodiment provides a method for preparing a modified ternary material. In the preparation method, in step (2), the mass ratio of the cobalt element in the cobalt source to the first modified material is adjusted from 0.01:1 to 0.03:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0081] Example 10
[0082] This embodiment provides a method for preparing a modified ternary material. In the preparation method, the temperature of the second sintering in step (2) is adjusted from 800° C. to 700° C. Except for the above, other conditions are exactly the same as those in Comparative Example 1.
[0083] Embodiment 11
[0084] This comparative example provides a method for preparing a modified ternary material. In the preparation method, the temperature of the second sintering in step (2) is adjusted from 800° C. to 740° C. Except for the above, other conditions are exactly the same as those in comparative example 1.
[0085] Example 12
[0086] This comparative example provides a method for preparing a modified ternary material. In the preparation method, the temperature of the second sintering in step (2) is adjusted from 800° C. to 830° C. Except for the above, other conditions are exactly the same as those in comparative example 1.
[0087] Comparative Example 1
[0088] This comparative example provides a method for preparing a modified ternary material, wherein the method does not use the non-cobalt metal source to form a non-cobalt metal superficial doping region, and the method comprises:
[0089] (1) First prepare the ternary material matrix, lithium hydroxide as the lithium source and nickel cobalt manganese hydroxide precursor Ni 0.75 Co 0.05 Mn 0.25 The molar ratio of lithium in the lithium source to the transition metal in the nickel-cobalt-manganese oxide is 1.04:1, and then calcined at 910°C for 12h in an oxygen atmosphere, and the hardened material is put into a jet mill and crushed until the particle size D 50 =3.9μm, and the single crystal ternary material matrix Li(Ni 0.75 Co 0.05 Mn 0.25 )O2;
[0090] (2) The obtained ternary material matrix and particle size D 50 A cobalt source cobalt hydroxide with a diameter of 0.6 μm is mixed with a flux boric acid, wherein the mass ratio of the flux to the cobalt source is 0.02:1, and the mass ratio of the cobalt element in the cobalt source to the ternary material matrix is 0.01:1, and then a second sintering is performed at 800° C. for 8 hours in an oxygen atmosphere to obtain a second modified material;
[0091] (3) The obtained second modified material is mixed with a coating agent of titanium dioxide, wherein the mass ratio of the metal element titanium in the coating agent to the second modified material is 0.0012:1, and a third sintering is performed at 400° C. for 10 hours in an air atmosphere to obtain a modified ternary material.
[0092] Comparative Example 2
[0093] This comparative example provides a method for preparing a modified ternary material, wherein non-cobalt metal doping is performed when preparing a ternary material matrix, and the preparation method comprises:
[0094] (1) First prepare the ternary material matrix, lithium hydroxide as the lithium source, nickel cobalt manganese hydroxide precursor Ni 0.75 Co 0.05 Mn 0.25 (OH)2 and particle size D 50 The non-cobalt metal source niobium pentoxide with a particle size of 0.3 μm is uniformly mixed, the molar ratio of the lithium element in the lithium source to the transition metal element in the nickel-cobalt-manganese oxide is 1.04:1, and the mass ratio of the non-cobalt metal element niobium in the non-cobalt metal source to the theoretically obtained ternary material matrix is 0.001:1; then calcining at 910°C for 12h in an oxygen atmosphere, and putting the agglomerated material into a jet mill for crushing until the particle size D 50 =3.9μm, and the single crystal ternary material matrix Li(Ni 0.75 Co 0.05 Mn 0.25 )O2;
[0095] (2) The obtained ternary material matrix and particle size D 50 A cobalt source cobalt hydroxide with a diameter of 0.6 μm is mixed with a flux boric acid, wherein the mass ratio of the flux to the cobalt source is 0.02:1, and the mass ratio of the cobalt element in the cobalt source to the ternary material matrix is 0.01:1, and then a second sintering is performed at 800° C. for 8 hours in an oxygen atmosphere to obtain a second modified material;
[0096] (3) The obtained second modified material is mixed with a coating agent of titanium dioxide, wherein the mass ratio of the metal element titanium in the coating agent to the second modified material is 0.0012:1, and a third sintering is performed at 400° C. for 10 hours in an air atmosphere to obtain a modified ternary material.
[0097] Characterization and Testing:
[0098] Ⅰ. The distribution of the content of cobalt in the modified ternary materials obtained in Example 1, Example 5, Example 8, Example 10 and Comparative Example 1 was tested by an energy dispersive spectrometer (EDS). Figure 1 As shown, there are cobalt gradient doping areas from the surface (100% distance from the center of the particle) to the center (0% distance from the center of the particle) in the five modified ternary cathode materials obtained, and the molar concentration (percentage) of the cobalt element gradually decreases from the surface to the inside and tends to be stable. Among them, the cobalt concentration gradient of the modified ternary materials obtained in Example 1, Example 5, Example 8 and Example 10 changes rapidly from the surface to 80% of the distance from the center of the particle, and the gradient difference is large. This area corresponds to the shallow surface area; Figure 2As shown in the figure, the dotted circle represents the boundary of the shallow area inside the particle, and the shallow area is the color-filled part between the dotted circle and the surface; after step (1), the non-cobalt metal element is only doped in the shallow area, rather than being doped into all areas of all bulk phases, which can hinder the subsequent cobalt doping and effectively reduce the doping depth of the cobalt element, so that the cobalt element is more concentrated in the shallow area to form a structure with a more significant gradient, rather than in the shallow area, that is, in the area between 80% of the distance from the center of the particle to the center, the cobalt concentration gradient changes slowly and the difference is small; as shown in the figure, the doped circle represents the boundary of the shallow area inside the particle, and the shallow area represents the color-filled part between the dotted circle and the surface; Figure 3 As shown, Figure 3 Different color depths represent different cobalt element concentrations. The darker the color, the higher the concentration (percentage). Figure 3 The cobalt concentration of the sample (left in the middle) is more concentrated in the shallow surface, and the cobalt concentration gradient from the shallow surface to the center of the particle tends to be stable. Figure 3 The cobalt concentration gradient in the middle right figure is relatively uniform throughout the particle. Figure 1 The curve slope is close to a constant value. Compared with Example 1, Example 5 and Example 8, the surface cobalt concentration of the material obtained in Example 10 is too high, and part of the cobalt additive is not effectively incorporated into the bulk phase. The distribution of cobalt element concentration in other examples is shown in Table 1.
[0099]
[0100] Note: In Table 1, in the second modified material, the concentration of cobalt element on the surface is recorded as a, the concentration of cobalt element at 80% of the distance from the center to the surface is recorded as b, and the concentration of cobalt element at 50% of the distance from the center to the surface is recorded as c; the concentration of cobalt element in the matrix of the ternary material is recorded as d; the cobalt element concentration refers to the percentage of the amount of cobalt element in the total amount of nickel, cobalt and manganese.
[0101] Ⅱ. The electrochemical performance of the ternary material matrix obtained in Examples 1-12 and Comparative Example 1 was tested. The prepared nickel-cobalt-manganese ternary positive electrode material was tested on the blue electric test system for performance such as capacity, cycle, initial DCR and high-temperature storage capacity retention rate. The specific test method is: the nickel-cobalt-manganese oxide ternary positive electrode material prepared in Example 1 is used as the positive electrode active material and mixed with acetylene black and PVDF as the positive electrode. The mass ratio of the positive electrode active material, acetylene black and PVDF is 95:3:2. The lithium sheet is used as the negative electrode, and the compaction density is 3.5g / cm 3 , assembled into button-type half-cell;
[0102] Capacity and initial DCR test steps: charge and discharge voltage is 3.0~4.4V, test temperature is 25℃, charge and discharge rate is 0.2C / 0.2C, initial DCR is tested at 100% SOC, pulse current is 1C, 10s.
[0103] Cycle test steps: charge and discharge voltage is 3.0~4.5V, test temperature is 45℃, and cycle charge and discharge rate is 1C / 1C.
[0104] Storage capacity retention rate process steps: charge and discharge voltage is 3.0~4.5V, test temperature is 55℃, charge to 100% SOC and then rest for 5 days.
[0105] The results are shown in Table 2.
[0106]
[0107] It can be seen from Table 2 that:
[0108] In the voltage range of 3.0-4.4V, at 25°C and 0.2C rate, compared with Comparative Example 1, the modified ternary positive electrode materials obtained in Examples 1-7 have obvious improvement effects in initial discharge capacity and cycle retention rate, and obvious reduction effect in initial DCR. This is because the gradient structure of the cobalt coating layer formed in Examples 1-7 is more reasonable, and the internal resistance is significantly reduced while the energy density is increased.
[0109] Compared with Comparative Example 2, the modified ternary positive electrode materials obtained in Examples 1-7 have a significant improvement effect in the initial discharge capacity and the cycle retention rate, and a significant reduction effect in the initial DCR. This is because the Nb element in Comparative Example 2 is not doped in the shallow surface layer of the material, but is nearly uniformly distributed in the bulk phase, thereby failing to regulate the doping depth of the cobalt element and failing to form an ideal cobalt distribution gradient structure.
[0110] Compared with Example 1 and Examples 2 to 5, as the doping amount of non-cobalt metal elements increases, it can be seen from Table 1 that the concentration of cobalt elements at the surface and 80% of the center to the surface increases slightly, which further reflects the regulating effect of the metal element on the doping depth of the cobalt element. In terms of charge retention performance, the capacity shows a downward trend, while the cycle retention rate shows a downward trend. It can be foreseen that when the doping amount of non-cobalt metal elements is too much, the kinetic properties of the material will be significantly reduced, and when the doping amount is too little, the cycle performance will be severely attenuated.
[0111] Comparing Example 1 with Examples 6 and 7, after the non-cobalt metal elements are replaced with W or Mo elements, the concentration gradient structure of the cobalt element in Table 1 does not show obvious changes, and there is no obvious difference in the electrical properties in Table 2. This proves that these elements have similar effects and can all serve the purpose of regulating the distribution gradient structure of the cobalt element and optimizing the electrical properties.
[0112] Compared with Example 1 and Examples 8 and 9, as the amount of cobalt source coating changes, the cobalt element is significantly increased on the particle surface and at 80% of the position from the center to the surface, but (ab) / (cd) is still between 3 and 10, which proves that non-cobalt metal elements can still play a role in regulating the gradient structure of the cobalt element distribution and does not change due to changes in the amount of cobalt element added.
[0113] Compared with Example 1 and Examples 10-12, the modified ternary cathode materials obtained in Examples 1, 11 and 12 have obvious advantages in high temperature storage capacity retention rate. This is because the cobalt element in the modified ternary cathode materials prepared in Examples 1, 11 and 12 does not just stay on the surface but is effectively incorporated into the bulk of the material, which greatly reduces the electrochemical reaction activity of the cobalt on the surface of the material and brings about many side reactions. This shows that for a specific ternary material matrix Li (Ni 0.75 Co 0.05 Mn 0.25 ) 2- For example, the preferred temperature range of the second sintering is 740-830°C. However, it should be noted that for other ternary material matrices, the most suitable temperature of the second sintering may vary to a certain extent and should be reasonably adjusted and selected.
[0114] From the above, it can be seen that the preparation method of the present invention directs the incorporation of non-cobalt metal elements with larger ionic radius into the shallow layer of the ternary material matrix in advance to form a barrier to block the subsequent cobalt doping, which can effectively reduce the incorporation depth of the cobalt element, thereby limiting more cobalt to the shallow surface layer of the particles, thereby forming a relatively uniform cobalt concentration change structure different from the conventional cobalt coating process. The cobalt concentration gradient structure of this process has the characteristics of high cobalt concentration in the shallow surface layer, fast concentration gradient change, and large concentration gradient difference, while the cobalt concentration gradient in the non-shallow surface area changes slowly and has a small gradient difference. After the second sintering to dope the cobalt element into the bulk phase and form a concentration gradient structure, the proportion of cobalt elements on the surface of the material is high due to the gradient decrease of the cobalt element concentration from the outside to the inside, which can improve the ionic conductivity of the material and thus reduce the material impedance and increase the energy density; at the same time, the cobalt concentration gradient doping structure formed by the particles as a whole is also conducive to improving the cycle performance. Finally, the surface of the material can be repaired by coating through the third sintering to obtain a modified ternary material with a complete coating layer, which can not only improve the ion transmission rate, but also reduce the side reaction between the particles and the electrolyte, prevent the cobalt concentration gradient distribution from being destroyed, thereby ensuring that the gradient doped cobalt element plays its due role. The preparation method is simple in process, fully compatible with existing production line mass production equipment, and the production process is easy to control, which is suitable for large-scale mass production.
[0115] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0116] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0117] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a modified ternary material, characterized in that: The steps include: (1) mixing a ternary material matrix with a non-cobalt metal source, and performing a first sintering to form a non-cobalt metal shallow doping region from the surface of the ternary material matrix to the inside, thereby obtaining a first modified material; wherein the ion radius of the non-cobalt metal element is greater than the ion radius of the cobalt element; (2) mixing the first modified material with a cobalt source and performing a second sintering to form a cobalt gradient doping region with a decreasing cobalt element concentration from the surface to the inside of the first modified material, thereby obtaining a second modified material; (3) The second modified material is mixed with a coating agent, and subjected to a third sintering to form a coating layer on the surface of the second modified material, thereby obtaining the modified ternary material.
2. The method for preparing the modified ternary material according to claim 1, characterized in that: In step (1), the non-cobalt metal element in the non-cobalt metal source includes at least one of W, Mo or Nb; the non-cobalt metal source includes an oxide; the particle size D of the non-cobalt metal source is 50 is 0.02-1 μm; the mass ratio of the non-cobalt metal element in the non-cobalt metal source to the ternary material matrix is (0.0005-0.005):1; The ternary material matrix includes a nickel-cobalt-manganese ternary material, the chemical formula of which is Li(Ni x Co y Mn z )O2, 1>x≥0.6, 0.2≥y>0, 0.4≥z>0, and x+y+z=1.
3. The method for preparing the modified ternary material according to claim 1, characterized in that: In step (1), the temperature of the first sintering is T1, T1=700~900°C, and the time is 4~15h.
4. The method for preparing the modified ternary material according to claim 1, characterized in that: In step (1), the coverage of the non-cobalt metal superficial doping region starts from the surface of the ternary material substrate and extends to a position of 80% to 99% from the center of the ternary material substrate to the surface.
5. The method for preparing the modified ternary material according to claim 1, characterized in that: In step (2), a flux is mixed with the first modified material and the cobalt source, and then the second sintering is performed; the flux includes a compound containing at least one of Li, B, P or F; the mass ratio of the flux to the cobalt source is (0.01-0.6):1; The particle size D of the cobalt source 50 The mass ratio of the cobalt element in the cobalt source to the first modified material is (0.005-0.03):
1.
6. The method for preparing the modified ternary material according to claim 4, characterized in that: In step (2), the second sintering temperature is T2, T2=650~850°C, and the time is 4~15h.
7. The method for preparing the modified ternary material according to claim 1, characterized in that: In step (2), in the second modified material, the concentration of cobalt element on the surface is denoted as a, the concentration of cobalt element at 80% of the distance from the center to the surface is denoted as b, and the concentration of cobalt element at 50% of the distance from the center to the surface is denoted as c; the concentration of cobalt element in the ternary material matrix is denoted as d; then, 10>(ab) / (cd)>3.
8. The method for preparing the modified ternary material according to claim 1, characterized in that: In step (3), the coating agent includes a compound containing at least one of Al, Zr, W, Ti, Mg, Nb, Zn, Fe, La, B, P or F; The mass ratio of the metal element in the coating agent to the second modified material is (0.0001-0.003):1; The temperature of the third sintering is T3, T3=250~550°C, and the time is 6~15h.
9. A modified ternary material, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery contains the modified ternary material according to claim 9.
Citation Information
Patent Citations
Positive electrode material, preparation method thereof and lithium ion battery
CN112750999A
Cobalt gradient high-nickel ternary positive electrode material, preparation method thereof and lithium ion battery
CN115259244A
Composite doped high-nickel large-single-crystal ternary layered oxide positive electrode material and preparation method and application thereof
CN115763749A
Lithium nickel cobalt manganese oxide positive electrode material, preparation method thereof and lithium ion battery
CN117790721A
Co gradient doped and coated ternary positive electrode material as well as preparation method and application thereof
CN117800407A